Soft Power and Great-Power Competition Shifting Sands in the Balance of Power Between the United States and China - Nye, Joseph S. (China and Globalization, 2023)
This open access book consists of essays selected from Joseph S. Nye, Jr.'s last three decades of writing and illustrate a variety of perspectives on the nature of power, the role of the United States in the world and US-China relations. Through this collection, it is hoped that readers will gain a better understanding of today's global environment and find that while great power competition may be inevitable in a world as centers of power shift, cooperating to address transnational challenges can be a positive sum game. The contents of this book are divided into four main parts. Part One discusses the origins and political progress of the concept of "Soft Power". Part Two explores soft power in the American experience, its sources and interaction with US foreign policy, as well as its ebb and flow in the age of Obama, Trump and Biden. Part Three examines the rise of and the opportunities and difficulties for Chinese soft power, focusing on China's investment in soft power and how this demonstrates its commitment to a peaceful rise. However, it also addresses the question of how can China get "smart" on how it uses soft power. Part Four provides a bird's-eye view of power shifts in the 21st century and the interactions between the US as an established power and China as a rising power, while also reassuring readers that Thucydidean fears are unnecessary and a Cold War is avoidable. Both countries have to realize that some forms of power must be exercised with others, not over others, the development of soft power need not be a zero-sum game. Ultimately, the US-China relationship is a "cooperative rivalry" where a successful strategy of "smart competition" is necessary and cooperation on transnational challenges like climate change, pandemics, cyberterrorism and nuclear proliferation, will serve to benefit not only China and the US, but the world as a whole.